Socialization of Stunting Prevention through Conseling and Providing Additional Food to Pregnant Woman and Toodlers - Diana Saputri R; Dian Riani Said; Gunawan; Achmad Dahlan (Yayasan Payungi Smart Madani, 2024)
Stunting or shortness is a condition of growth failure in children due to chronic nutritional deficiency, especially in the first 1000 Days of Life (HPK), making the child too short for their age. The issue of stunting has become an important issue that must be addressed collectively. Factors such as poverty, inadequate nutritional intake, and low knowledge are the main factors that must be faced to prevent stunting. Prevention of stunting must be done as early as possible, starting from when the fetus is still in the womb. One way to reduce stunting is by increasing awareness of stunting through socialization and assistance. The methods used are lectures, question and answer sessions, or interviews with the community in Siwal Village, Sukoharjo Regency, Central Java Province, related to the prevention of stunting through socialization and assistance using media such as leaflets, PowerPoint, and other supporting tools. The results and implementation include providing supplementary food to pregnant women and toddlers, education and socialization for pregnant women, and efforts to prevent stunting, as well as educating the community of Siwal Village, Sukoharjo Regency, Central Java Province, about understanding stunting or adequate nutritional intake for pregnant women and toddlers, as well as informing about the dangers of stunting.